Religious Tolerance in the Constitution and Guarantees for the Protection of Human Rights (Universitas Negeri Semarang, 2022)
Protection of human rights is an absolute guarantee that must be fulfilled by the rule of law. Article 1 Paragraph 3 of the 1945 Constitution of the Republic of Indonesia mandates that